Evaluating NHS Stop Smoking Service engagement in community pharmacies using simulated smokers: fidelity assessment of a theory-based intervention. Issue 5 (19th May 2019) - Jumbe, Sandra; James, Wai Y; Madurasinghe, Vichithranie; Steed, Liz; Sohanpal, Ratna; Yau, Tammy K; Taylor, Stephanie; Eldridge, Sandra; Griffiths, Chris; Walton, Robert
Abstract : Objectives: Smokers are more likely to quit if they use the National Health Service (NHS) Stop Smoking Service (SSS). However, community pharmacies experience low service uptake. The Smoking Treatment Optimisation in Pharmacies (STOP) programme aims to address this problem by enhancing staff training using a theory-based intervention. In this study, we evaluated intervention fidelity using simulated smokers (actors) to assess smoker engagement and enactment of key intervention components by STOP trained staff. Design: An observational pilot study. Settings: Five community pharmacies in North East London with an NHS SSS. Methods: Six actors, representative of East London's population, were recruited and trained to complete intervention fidelity assessments. Consenting pharmacy staff from five participating pharmacies received STOP Intervention training. Four weeks after the staff training, the actors visited the participating pharmacies posing as smokers eligible for smoking cessation support. Engagement behaviour by pharmacy staff and enactment of intervention components was assessed using a scoring tool derived from the STOP logic model (scoring range of 0–36), and contemporaneous field notes taken by actors. Results: 18 of 30 completed assessments were with STOP trained staff (10/18 were counter assistants). Mean score for smoker engagement was 24.4 (SD 9.0) points for trained and 16.9 (SD 7.8) for untrained staff, respectively. NHS SSS leaflets (27/30) were the most common smoking cessation materials seen on pharmacy visits. Most trained counter staff engaged with smokers using leaflets and a few proactively offered appointments with their cessation advisors. Appropriate use of body language was reported on 26/30 occasions alongside the use of key phrases from the STOP training session (n=8). Very few pharmacy staff wore STOP promotional badges (4/30). Conclusions: STOP training may change client engagement behaviour in pharmacy staff and could improve the uptake of the NHS SSS. A cluster randomised controlled trial is currently in progress to evaluate its effectiveness and cost-effectiveness. Trial registration number: ISRCTN16351033 .